O futebol: cultura e convergência das mídias - Rohrer, Cleber Vanderlei (2016)
This research analyses how football is part of Brazilian culture because of its playful aspect, with elements in its daily routine and language, and how it is presented in the media. The history of football in the media is observed with the aim of establishing the connection between this sport and means of communication, besides showing the modifications and adjustments the language has undergone to follow the changes that occurred with the advance in technology. Highlights include how media convergence has changed the way fans watch the matches on digital television, internet and mobile devices. The process of convergence is analysed from the concepts presented by Jesus Martín-Barbero, Pierre Lévy, Henry Jenkins and Lucia Leão, backed up by sport sociological studies of Norbert Elias e Eric Dunning. World Cup and Olympics are events that always bring new technologies that directly impact sports broadcasts for both professionals and fans.During these events held in Brazil, in 2014 and 2016, respectively, besides the traditional media - such as radio, television and newspapers - the internet and mobile devices, as tablets and cell phones, increased the possibilities for fans to watch the matches. Research shows that fans assimilate new technologies through mobile devices without forgetting radio and television broadcasting. Another point to emphasize is that new technologies not only change the way fans watch the matches but also are assimilated into football structure. This study analysed Brazilian Football Championship matches and the new stadiums' operation, such as Allianz Parque and Arena Corinthians. Several teams’ supporters were interviewed in order to analyse how they watch the football matches and to determine the importance of sport in their lives